Dampak dan Peran Politik terhadap Pembangunan Infrastruktur dan Pemberdayaan Sosial Ekonomi Masyarakat Lombok Utara - Hafadzatun Adzmi; Maemunah Maemunah; Isnaini Isnaini (Universitas Pendidikan Ganesha, 2024)
Politics plays a crucial role in determining the direction of infrastructure development and socioeconomic empowerment of the community in North Lombok. Development is inherently linked to government policies and practices, particularly in realizing the nation's aspirations for social justice for all Indonesian citizens. The people of North Lombok tend to expect political support in infrastructure development and community empowerment programs such as training, skill development, and economic empowerment for women rather than participating in politics to improve family economics. They also believe that political support can enhance access to education, healthcare, and other essential services but need more confidence in allocating budget funds according to the needs of the North Lombok community. This research focuses on measuring the extent to which community well-being, particularly in terms of infrastructure and socioeconomic aspects, is influenced by political involvement. Data analysis is conducted in two stages: descriptive statistics and linear regression analysis. The research findings indicate a significant influence of political involvement on infrastructure development, accounting for 45.3% of the variance. Political engagement also significantly impacts the socioeconomic empowerment of the North Lombok community, explaining 47% of the variance. This study has important implications for policymakers who want to consider political factors in the planning and implementing development and community empowerment programs in the North Lombok region.